2017
DOI: 10.1007/s10508-017-0990-9
|View full text |Cite
|
Sign up to set email alerts
|

Gay Men’s Health and Identity: Social Change and the Life Course

Abstract: Due to significant historical change in the late twentieth and early twenty-first century related to both health and cultural attitudes toward homosexuality, gay men of distinct birth cohorts may diverge considerably in their health and identity development. We argue that research on gay men’s health has not adequately considered the significance of membership in distinct generation-cohorts, and we present a life course paradigm to address this problem. Focusing on the United States as an exemplar that can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
118
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 146 publications
1
118
0
2
Order By: Relevance
“…Taking an intersectional lens [Coston & Kimmel, 2012], I concluded that the data corpus comprised interviews from gay men of relative privilege in US society: privileged with regard to race, class, education, and accessibility of LGBTQ resources based on urban and suburban upbringing. I calculated that the majority of men were born in the late 1980s and early 1990s, members of what I and others have dubbed the "Equality Generation" of gay men because they experienced their adolescence at the height of the marriage equality movement [Hammack et al, 2018]. Savin-Williams [2016] acknowledges that these men are "not 'representative' of young gay men in the United States" (p. 301).…”
Section: A Note On Genre and Data Corpusmentioning
confidence: 99%
See 4 more Smart Citations
“…Taking an intersectional lens [Coston & Kimmel, 2012], I concluded that the data corpus comprised interviews from gay men of relative privilege in US society: privileged with regard to race, class, education, and accessibility of LGBTQ resources based on urban and suburban upbringing. I calculated that the majority of men were born in the late 1980s and early 1990s, members of what I and others have dubbed the "Equality Generation" of gay men because they experienced their adolescence at the height of the marriage equality movement [Hammack et al, 2018]. Savin-Williams [2016] acknowledges that these men are "not 'representative' of young gay men in the United States" (p. 301).…”
Section: A Note On Genre and Data Corpusmentioning
confidence: 99%
“…The explosion of research on the biological basis of homosexuality likely contributed to shifts in cultural perspectives and rhetoric toward greater acceptance [e.g., Hamer & Copeland, 1994;LeVay, 1996]. These men experienced their adolescence in the 2000s with the thrust of the marriage equality movement which, though it took time, resulted in an enormous civil rights victory for individuals with same-sex desire: the attainment of the legal right to marry throughout the USA [Hammack et al, 2018].…”
Section: Gay Men's Identities: Twenty-first Century Storiesmentioning
confidence: 99%
See 3 more Smart Citations